Two new critically endangered species of Hippeastrum (Amaryllidaceae) from the Brazilian Cerrado - Campos-Rocha, Antonio; Meerow, Alan William; Dutilh, Julie Henriette Antoinette (Phytotaxa, 2018)
Monographic work on the genus Hippeastrum in Brazil has revealed two new species endemic to the Cerrado biome, here described and illustrated. Hippeastrum lunaris is a species restricted to the region of Chapada dos Veadeiros; H. mauroi is so far found only in Chapada dos Guimarães. Detailed descriptions, illustrations and taxonomic comments on the conservation status of these species are provided, in addition to comparisons with morphologically similar species. An identification key to the species of Hippeastrum occurring in the Brazilian Cerrado is presented, accompanied by photographs of these species in their natural habitats.